Saccharomyces spores are born prepolarized to outgrow away from spore–spore connections and penetrate the ascus wall. Issue 1 (7th December 2020) - Heasley, Lydia R.; Singer, Emily; Cooperman, Benjamin J.; McMurray, Michael A.
Abstract: How nonspore haploid Saccharomyces cells choose sites of budding and polarize towards pheromone signals in order to mate has been a subject of intense study. Unlike nonspore haploids, sibling spores produced via meiosis and sporulation by a diploid cell are physically interconnected and encased in a sac derived from the old cell wall of the diploid, called the ascus. Nonspore haploids bud adjacent to previous sites of budding, relying on stable cortical landmarks laid down during prior divisions, but because spore membranes are made de novo, it was assumed that, as is known for fission yeast, Saccharomyces spores break symmetry and polarize at random locations. Here, we show that this assumption is incorrect: Saccharomyces cerevisiae spores are born prepolarized to outgrow, prior to budding or mating, away from interspore bridges. Consequently, when spores bud within an intact ascus, their buds locally penetrate the ascus wall, and when they mate, the resulting zygotes adopt a unique morphology reflective of repolarization towards pheromone. Long‐lived cortical foci containing the septin Cdc10 mark polarity sites, but the canonical bud site selection programme is dispensable for spore polarity, thus the origin and molecular composition of these landmarks remain unknown. These findings demand further investigation of previously overlooked mechanisms of polarity establishment and local cell wall digestion and highlight how a key step in the Saccharomyces life cycle has been historically neglected. Abstract : When budding yeast spores germinate, they outgrow away from each other, following cortical foci of the septin protein Cdc10. If spores then bud, and old cell wall of the mother diploid cell still surrounds them, the buds locally penetrate that wall. If spores instead mate with each other, their outward prepolarization leads to a unique zygote morphology. Prepolarization does not require Rsr1, a key component of the canonical bud site selection pathway in nonspore cells.